Shape memory cyanate ester composite material as well as preparation method and application thereof

Through the organic solvent toughening method, the problems of high brittleness and poor durability of traditional shape memory cyanate composite materials are solved, which significantly improves the toughness and durability of the material, and is suitable for applications in high-performance engineering fields.

CN119912811APending Publication Date: 2025-05-02LANZHOU INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510192439.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-21
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

Traditional shape memory cyanate composites have problems such as high brittleness, poor durability and difficulty in withstand complex mechanical stresses in practical applications, which limits their application in the field of high-performance engineering.

Method used

The shape memory cyanate composite material is prepared by thermally mixing cyanate esters, flexible molecular segment monomers and organic solvents. This method is simple and has a wide range of applications, and can significantly improve the toughness and durability of the material.

Benefits of technology

It significantly improves the elongation of shape memory cyanate composite material break, solves the problem of brittle cracking, maintains high shape recovery rate and rapid recovery speed, and improves the toughness and durability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119912811A_ABST
    Figure CN119912811A_ABST
Patent Text Reader

Abstract

The invention provides a shape memory cyanate ester composite material as well as a preparation method and application thereof, and relates to a shape memory material. The invention provides a preparation method of a shape memory cyanate ester composite material, which comprises the following steps: thermally mixing cyanate ester, a monomer with a flexible molecular chain segment and an organic solvent, and curing to obtain the shape memory cyanate ester composite material, the organic solvent is prepared from one or more of N, N-dimethylacetamide, acetonitrile, propionitrile, methylbenzene, dimethyl sulfoxide, pyridine, p-xylene, o-xylene, m-xylene, ethyl acetate and N-methyl pyrrolidone; the ratio of the mass of the cyanate ester to the volume of the organic solvent is 1g: (0.1-0.8) mL. The organic solvent is adopted for toughening, the toughness and durability of the shape memory cyanate ester composite material can be remarkably improved on the basis of ensuring the shape memory characteristic, and the toughening method is simple and wide in application range.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of shape memory materials, and in particular to a shape memory cyanate ester composite material and a preparation method and application thereof. Background Art

[0002] Shape memory polymer composites are a type of polymer material that can restore its original shape under external stimuli (such as temperature, light or electric field). Compared with shape memory polymers, shape memory polymer composites have more excellent properties, such as photothermal conversion, high thermal conductivity, high tensile strength, wear resistance and corrosion resistance, etc., and are widely used. For example, in the field of aerospace, cyanate ester composites as a polymer with excellent performance have been used in radomes and other fields. For more complex application conditions, traditional cyanate ester polymers cannot meet actual needs, so it is necessary to give cyanate ester polymers a shape memory effect. However, traditional shape memory cyanate ester composites often face problems such as greater brittleness, poor durability and difficulty in withstanding complex mechanical stresses in actual applications, which limits their application in some high-performance engineering fields.

[0003] To solve these problems, researchers have introduced different types of toughening agents to improve the toughness of shape memory cyanate ester composites. Although the toughening method of toughening agents can significantly improve its toughness, ductility and impact resistance, this method is limited by the type and content of toughening agents, resulting in failure to meet the growing demand. Therefore, a simpler and more widely applicable toughening method is needed while maintaining the shape memory effect. Summary of the invention

[0004] In view of this, the object of the present invention is to provide a shape memory cyanate ester composite material and its preparation method and application. The present invention uses organic solvent for toughening, the toughening method is simple and has a wide range of applications, and the prepared composite material has shape memory properties and high toughness.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a method for preparing a shape memory cyanate ester composite material, comprising the following steps:

[0007] The cyanate ester, the monomer with a flexible molecular chain segment and the organic solvent are thermally mixed and then cured to obtain a shape memory cyanate ester composite material;

[0008] The organic solvent includes one or more of N,N-dimethylacetamide, acetonitrile, propionitrile, toluene, dimethyl sulfoxide, pyridine, p-xylene, o-xylene, m-xylene, ethyl acetate and N-methylpyrrolidone;

[0009] The ratio of the mass of the cyanate ester to the volume of the organic solvent is 1 g: 0.1-0.8 mL.

[0010] Preferably, the cyanate ester includes one or more of bisphenol A cyanate ester, bisphenol E cyanate ester and multifunctional cyanate ester resin;

[0011] The multifunctional cyanate ester resin has a structure shown in Formula I:

[0012]

[0013] Among them, R includes or -OCN.

[0014] Preferably, the monomer having a flexible molecular chain segment includes one or more of epoxy GE36, polycaprolactone diol, polytetramethylene glycol, polycarbonate diol and polyethylene glycol;

[0015] The mass ratio of the cyanate ester to the monomer having a flexible molecular chain segment is 1:0.3-1.2.

[0016] Preferably, the hot mixed raw material further comprises a filler, and the filler comprises one or more of graphene oxide, carbon nanotube oxide, graphene, carbon fiber and silicon dioxide;

[0017] The mass ratio of the cyanate ester to the filler is 1:0.02-0.2.

[0018] Preferably, the temperature of the thermal mixing is 80-100° C. and the time is 1-3 hours.

[0019] Preferably, the curing is programmed curing, which includes first curing, second curing and third curing in sequence; the temperature of the first curing is 100-140°C, and the insulation time is 2-4 hours; the temperature of the second curing is 140-160°C, and the insulation time is 1-4 hours; the temperature of the third curing is 170-200°C, and the insulation time is 1-4 hours.

[0020] Preferably, after the thermal mixing, the method further comprises: removing bubbles from the mixed liquid obtained by the thermal mixing.

[0021] Preferably, the degassing temperature is 40 to 120° C. and the time is 10 to 60 minutes.

[0022] The present invention also provides a shape memory cyanate ester composite material prepared by the preparation method described in the above technical solution.

[0023] The present invention also provides the use of the shape memory cyanate ester composite material described in the above technical solution in fighter jets or smart molds.

[0024] The present invention adopts a specific solvent toughening method, which can significantly improve the elongation at break of the shape memory cyanate ester composite material while ensuring the shape memory property. Compared with the traditional toughening method, the present invention solves the problem that the existing shape memory cyanate ester composite material is easy to brittle. The shape memory cyanate ester composite material prepared by the present invention can effectively maintain its shape memory property during the toughening process, has a high shape recovery rate and a fast recovery speed, and maintains a very high shape deformation ability. The toughening method provided by the present invention not only improves the toughness of the shape memory cyanate ester composite material, but also this simple preparation method reduces the requirements for process conditions, and the toughening method is simple and has a wide range of applications. The present invention significantly improves the toughness and durability of the shape memory polymer by selecting a reasonable type of organic solvent and controlling the dosage ratio of the organic solvent. The shape memory cyanate ester composite material prepared by the present invention has high tensile strength, high toughness, good durability, and good shape memory property, and is expected to be used in the fields of intelligent skins of advanced fighters and intelligent molds for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a diagram of the large deformation and recovery process of the shape memory cyanate ester composite material prepared in Example 1 to simulate the fighter skin. DETAILED DESCRIPTION

[0026] The invention provides a method for preparing a shape memory cyanate ester composite material, comprising the following steps: hot-mixing cyanate ester, a monomer having a flexible molecular segment and an organic solvent and then curing the mixture to obtain the shape memory cyanate ester composite material.

[0027] Unless otherwise specified, the materials and equipment used in the present invention are all commercially available products in the art.

[0028] In the present invention, the cyanate ester preferably includes one or more of bisphenol A cyanate ester, bisphenol E cyanate ester and multifunctional cyanate ester resin. In the present invention, the multifunctional cyanate ester resin preferably has a structure shown in Formula I:

[0029]

[0030] Among them, R includes or -OCN.

[0031] In the present invention, the monomer with flexible molecular chain segments preferably includes one or more of epoxy GE36, polycaprolactone diol, polytetrahydrofuran diol, polycarbonate diol and polyethylene glycol. In the present invention, flexible molecular chain segments are added to cyanate ester to reduce the crosslinking density, thereby improving the toughness of the material.

[0032] In the present invention, the mass ratio of the cyanate ester to the monomer having a flexible molecular segment is preferably 1:0.3-1.2, and in specific embodiments may be 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1, 1:1.1 or 1:1.2.

[0033] In the present invention, the organic solvent includes one or more of N,N-dimethylacetamide, acetonitrile, propionitrile, toluene, dimethyl sulfoxide, pyridine, p-xylene, o-xylene, m-xylene, ethyl acetate and N-methylpyrrolidone. In the present invention, the ratio of the mass of the cyanate ester to the volume of the organic solvent is 1g: 0.1-0.8mL, and in specific embodiments it can be 1g: 0.1mL, 1g: 0.2mL, 1g: 0.3mL, 1g: 0.4mL, 1g: 0.5mL, 1g: 0.6mL, 1g: 0.7mL or 1g: 0.8mL. The present invention increases the space between the molecular structures and reduces the steric hindrance by adding a specific organic solvent and controlling its dosage, thereby playing a role in further improving the toughness of the material.

[0034] In the present invention, the hot mixed raw materials preferably also include fillers, and the hot mixing preferably includes: hot mixing cyanate, monomers with flexible molecular segments, fillers and organic solvents. In the present invention, the filler preferably includes one or more of graphene oxide, oxidized carbon nanotubes, graphene, carbon fiber and silicon dioxide. In the present invention, the mass ratio of the cyanate and the filler is preferably 1:0.02-0.2, and in specific embodiments it can be 1:0.02, 1:0.03, 1:0.04, 1:0.05, 1:0.06, 1:0.07, 1:0.08, 1:0.09, 1:0.1, 1:0.11, 1:0.12, 1:0.13, 1:0.14, 1:0.15, 1:0.16, 1:0.17, 1:0.18, 1:0.19 or 1:0.2. The present invention can improve the temperature resistance, wear resistance and corrosion resistance of the material by adding fillers.

[0035] In the present invention, the heat mixing temperature is preferably 80-100°C, and in specific embodiments it can be 80°C, 85°C, 90°C, 95°C or 100°C; the heat mixing time is preferably 1-3h, and in specific embodiments it can be 1h, 1.5h, 2h, 2.5h or 3h.

[0036] After the hot mixing, the present invention also preferably removes bubbles from the mixed solution obtained by the hot mixing. In the present invention, the bubble removal is preferably vacuum bubble removal. In the present invention, the bubble removal temperature is preferably 40 to 120°C, and in specific embodiments it can be 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C or 120°C, and the time is preferably 10 to 60 minutes, and in specific embodiments it can be 10 minutes, 20 minutes, 30 minutes, 40 minutes, 50 minutes or 60 minutes.

[0037] In the present invention, the curing is preferably programmed curing, and the programmed curing preferably includes sequentially performing a first curing, a second curing and a third curing; the temperature of the first curing is preferably 100-140°C, and in a specific embodiment, it can be 100°C, 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, 135°C or 140°C; the holding time of the first curing is preferably 2-4h, and in a specific embodiment, it can be 2h, 2.5h, 3h, 3.5h or 4h; the temperature of the second curing is preferably 140-160°C, and in a specific embodiment, it can be 100°C, 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, 135°C or 140°C. In the embodiment, it can be 140℃, 145℃, 150℃, 155℃ or 160℃; the holding time is preferably 1-4h, and in the specific embodiment, it can be 1h, 1.5h, 2h, 2.5h, 3h, 3.5h or 4h; the temperature of the third curing is preferably 170-200℃, and in the specific embodiment, it can be 170℃, 175℃, 180℃, 185℃, 190℃, 195℃ or 200℃, and the holding time is preferably 1-4h, and in the specific embodiment, it can be 1h, 1.5h, 2h, 2.5h, 3h, 3.5h or 4h. In the present invention, the holding temperatures of the first curing, the second curing and the third curing are increased in sequence. In the present invention, the curing is preferably carried out in a sealed mold to reduce the volatilization of organic solvents. The present invention has no special restrictions on the mold and the sealing method, and the mold and the sealing method well known to those skilled in the art can be used.

[0038] The present invention also provides a shape memory cyanate ester composite material prepared by the preparation method described in the above technical solution.

[0039] The present invention also provides the use of the shape memory cyanate ester composite material described in the above technical solution in a fighter or a smart mold; the shape memory cyanate ester composite material is preferably used for the smart skin of a fighter; the smart mold is preferably a smart mold used in the integrated molding process of large and complex devices. The shape memory cyanate ester composite material prepared by the present invention has high tensile strength, high toughness, good durability, and good shape memory properties, and is expected to be used in the fields of smart skin of advanced fighters and smart molds for industrial production.

[0040] In order to further illustrate the present invention, the shape memory cyanate ester composite material provided by the present invention and its preparation method and application are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0041] In the following examples, bisphenol A cyanate (CE) was purchased from Wuhan Lanabai Pharmaceutical Chemical Co., Ltd., China; polytetrahydrofuran diol was purchased from Jining Hongming Chemical Reagent Co., Ltd.; and polycarbonate diol was purchased from Jining Hongming Chemical Reagent Co., Ltd.

[0042] Example 1

[0043] Bisphenol A cyanate, polycarbonate diol, graphene oxide and N, N-dimethylacetamide were mixed at 90°C for 1 hour, and then the mixture was vacuumed at 80°C to remove bubbles for 30 minutes, poured into a mold with a groove, and then a polytetrafluoroethylene plate was pressed on the mold to maintain a sealed space, and the sealed mold was placed in an oven for curing. The curing procedure was 120°C for 3 hours, then 150°C for 2 hours, and then 180°C for 2 hours (the curing procedure was recorded as 120°C / 3h+150°C / 2h+180°C / 2h), and a solvent-toughened shape memory cyanate composite material was obtained. Among them, the mass ratio of bisphenol A cyanate, polycarbonate diol and graphene oxide was 1:0.6:0.04, and the mass ratio of bisphenol A cyanate to the volume of N, N-dimethylacetamide was 1g:0.4mL.

[0044] Example 2

[0045] Bisphenol A cyanate, polycarbonate diol, graphene oxide and N, N-dimethylacetamide were mixed at 90°C for 1 hour, and then the mixture was vacuumed and debubbled at 100°C for 30 minutes, poured into a mold with a groove, and then a PTFE plate was pressed on the mold to maintain a sealed space, and the sealed mold was placed in an oven for curing. The curing procedure was 120°C / 3h+150°C / 2h+180°C / 2h to obtain a solvent-toughened shape memory cyanate composite material. Among them, the mass ratio of bisphenol A cyanate, polycarbonate diol and graphene oxide was 1:0.6:0.04, and the mass ratio of bisphenol A cyanate to the volume of N, N-dimethylacetamide was 1g:0.4mL.

[0046] Example 3

[0047] Bisphenol A cyanate, polycarbonate diol, graphene oxide and N, N-dimethylacetamide were mixed at 90°C for 1 hour, and then the mixture was vacuumed at 120°C to remove bubbles for 30 minutes, poured into a mold with a groove, and then a PTFE plate was pressed on the mold to maintain a sealed space, and the sealed mold was placed in an oven for curing. The curing procedure was 120°C / 3h+150°C / 2h+180°C / 2h to obtain a solvent-toughened shape memory cyanate composite material. Among them, the mass ratio of bisphenol A cyanate, polycarbonate diol and graphene oxide was 1:0.6:0.04, and the mass ratio of bisphenol A cyanate to the volume of N, N-dimethylacetamide was 1g:0.4mL.

[0048] Example 4

[0049] Bisphenol A cyanate, polycarbonate diol, graphene oxide and toluene were mixed at 90°C for 1 hour, and then the mixture was vacuumed at 80°C to remove bubbles for 15 minutes, poured into a mold with a groove, and then a PTFE plate was pressed on the mold to maintain a sealed space, and the sealed mold was placed in an oven for curing. The curing procedure was 120°C / 3h+150°C / 2h+180°C / 2h to obtain a solvent-toughened shape memory cyanate composite material. Among them, the mass ratio of bisphenol A cyanate, polycarbonate diol and graphene oxide was 1:0.5:0.03, and the mass ratio of bisphenol A cyanate to the volume of toluene was 1g:0.2mL.

[0050] Example 5

[0051] Bisphenol A cyanate, polytetrahydrofuran diol, graphene oxide and dimethyl sulfoxide were mixed at 90°C for 1 hour, and then the mixture was vacuumed at 80°C to remove bubbles for 30 minutes, poured into a mold with a groove, and then a polytetrafluoroethylene plate was pressed on the mold to maintain a sealed space, and the sealed mold was placed in an oven for curing. The curing procedure was 120°C / 3h+150°C / 2h+180°C / 2h to obtain a solvent-toughened shape memory cyanate composite material. Among them, the mass ratio of bisphenol A cyanate, polytetrahydrofuran diol and graphene oxide was 1:0.6:0.08, and the mass ratio of bisphenol A cyanate to the volume of dimethyl sulfoxide was 1g:0.2mL.

[0052] Comparative Example 1

[0053] Bisphenol A cyanate, polytetrahydrofuran diol and graphene oxide were mixed at 90°C for 1 hour, and then the mixture was vacuumed at 80°C to remove bubbles for 30 minutes, poured into a mold with a groove, and then a polytetrafluoroethylene plate was pressed on the mold to maintain a sealed space, and the sealed mold was placed in an oven for curing. The curing procedure was 120°C for 3 hours, then 150°C for 2 hours, and then 180°C for 2 hours (the curing procedure was recorded as 120°C / 3h+150°C / 2h+180°C / 2h), and a solvent-toughened shape memory cyanate composite material was obtained. Among them, the mass ratio of bisphenol A cyanate, polytetrahydrofuran diol and graphene oxide was 1:0.6:0.08, and the mass ratio of bisphenol A cyanate to the volume of N,N-dimethylacetamide was 1g:0.4mL.

[0054] Test Case

[0055] According to the standard ISO 527-2 / 1BB, the samples were cut into dumbbells with a length of 30 mm, and the mechanical properties of the materials were tested at a rate of 5 mm / min using a universal tensile testing machine at room temperature. The mechanical properties of the materials were tested using a universal tensile testing machine. The shape fixation rate and shape recovery rate of the materials were tested by bending tests. The results are shown in Table 1.

[0056] Table 1 Performance test results of shape memory cyanate ester composite materials prepared in Examples and Comparative Examples

[0057]

[0058]

[0059] It can be seen from Table 1 that the shape memory cyanate ester composite material prepared in the embodiment of the present invention has a tensile strength of 33.2-48.6 MPa, an elongation at break of 24.4-61.3%, a Young's modulus of 910-1337 MPa, a shape recovery rate of more than 99%, a shape fixation rate of 92-99%, high tensile strength, high toughness, good durability, and good shape memory performance.

[0060] Through the tensile test, it can be analyzed that the organic solvent has a great influence on the mechanical properties of the material. Because in the process of degassing, different temperatures can lead to different amounts of organic solvent volatilization, thus making the material have different properties. At the same time, different types of organic solvents also lead to different properties of the material. But in general, the elongation at break of the shape memory cyanate ester composite material prepared by adding organic solvent is much higher than the shape memory cyanate ester composite material prepared in Comparative Example 1 without adding organic solvent.

[0061] Moreover, the toughening effect of organic solvents is also reflected in the shape memory effect of the material. The lower the temperature when removing bubbles, the higher the solvent content in the material, the smaller the steric hindrance between molecular segments, and the lower the steric hindrance, the more conducive to the shape recovery of the material. Moreover, the higher the boiling point of the organic solvent, the higher the shape recovery rate of the material.

[0062] Comparative Example 1 adopts the conventional toughening method - adding flexible molecular segments to cyanate ester to reduce the crosslinking density and improve the toughness of the material. The present invention uses conventional toughening (i.e. adding monomers with flexible molecular segments) and then adding a solvent to increase the space between molecular structures and reduce steric hindrance, thereby further improving the toughness of the material.

[0063] Figure 1 This is a diagram of the deformation and recovery process of the fighter skin simulated by the shape memory cyanate ester composite material prepared in Example 1. It can be seen that in the case of large deformation, the shape memory cyanate ester composite material can still achieve 100% recovery within 20 seconds. The rapid and complete recovery of the temporary shape of the shape memory cyanate ester composite material can meet practical application requirements.

[0064] In summary, the present invention adopts a specific organic solvent and controls its dosage ratio, which not only improves the mechanical properties of the shape memory cyanate ester composite material, but also effectively maintains its shape memory characteristics. The shape memory cyanate ester composite material prepared in this way is expected to be used in the fields of intelligent skins of advanced fighter jets and intelligent molds for industrial production.

[0065] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a shape memory cyanate ester composite material, characterized in that: The following steps are involved: The cyanate ester, the monomer with a flexible molecular chain segment and the organic solvent are thermally mixed and then cured to obtain a shape memory cyanate ester composite material; The organic solvent includes one or more of N,N-dimethylacetamide, acetonitrile, propionitrile, toluene, dimethyl sulfoxide, pyridine, p-xylene, o-xylene, m-xylene, ethyl acetate and N-methylpyrrolidone; The ratio of the mass of the cyanate ester to the volume of the organic solvent is 1 g: 0.1-0.8 mL.

2. The preparation method according to claim 1, characterized in that: The cyanate ester includes one or more of bisphenol A cyanate ester, bisphenol E cyanate ester and multifunctional cyanate ester resin; The multifunctional cyanate ester resin has a structure shown in Formula I: Among them, R includes or -OCN.

3. The preparation method according to claim 1, characterized in that: The monomer with flexible molecular chain segment includes one or more of epoxy GE36, polycaprolactone diol, polytetramethylene glycol, polycarbonate diol and polyethylene glycol; The mass ratio of the cyanate ester to the monomer having a flexible molecular chain segment is 1:0.3-1.

2.

4. The preparation method according to claim 1, characterized in that: The hot mixed raw materials further include fillers, wherein the fillers include one or more of graphene oxide, oxidized carbon nanotubes, graphene, carbon fiber and silicon dioxide; The mass ratio of the cyanate ester to the filler is 1:0.02-0.

2.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The temperature of the hot mixing is 80-100° C. and the time is 1-3 hours.

6. The preparation method according to claim 1, characterized in that: The curing is programmed curing, which includes first curing, second curing and third curing in sequence; the temperature of the first curing is 100-140°C, and the insulation time is 2-4 hours; the temperature of the second curing is 140-160°C, and the insulation time is 1-4 hours; the temperature of the third curing is 170-200°C, and the insulation time is 1-4 hours.

7. The preparation method according to claim 5, characterized in that: After the thermal mixing, the method further comprises: removing bubbles from the mixed liquid obtained by the thermal mixing.

8. The preparation method according to claim 7, characterized in that: The temperature of the degassing process is 40 to 120° C. and the time is 10 to 60 minutes.

9. The shape memory cyanate ester composite material obtained by the preparation method according to any one of claims 1 to 8.

10. Use of the shape memory cyanate ester composite material according to claim 9 in fighter jets or smart molds.